Spontaneous Uterine Rupture in a Preterm Pregnancy following Myomectomy. (26th January 2016) - Sutton, Claire; Standen, Prue; Acton, Jade; Griffin, Christopher
Abstract : A 44-year-old nulliparous woman was transferred to a tertiary obstetric hospital for investigation of acute onset abdominal pain. She was at gestation of 32 weeks and 2 days with a history of previous laparoscopic fundal myomectomy. An initial bedside ultrasound demonstrated oligohydramnios. Following an episode of increased pain early the following morning, a formal ultrasound diagnosed a uterine rupture with the fetal arm extending through a uterine rent. An uncomplicated classical caesarean section was performed and the neonate was delivered in good condition but with a bruised and oedematous right arm. The neonate was transferred to the Special Care Nursery for neonatal care. The patient had an uncomplicated postoperative course and was discharged home three days following delivery. This is an unusual presentation of uterine rupture following myomectomy where the fetal arm had protruded through the uterine wall.